Conceptual Metaphor of Eliot’s Waste Land Versus Al-Sayyab’s Rain Song - Ibrahim Ayassrah, Mohamed Ayed; Latiff Azmi, Mohd Nazri (KnE Social Sciences, 2019)
Of the rhetorical tools, metaphor still has insufficient interest, primarily as a crosscultural phenomenon though it is an attractive and vivid area, so it should be studied and highlighted (Suhadi, 2018) and (Barton, 2017). This comparative study investigated the conceptual metaphor in modern Arabic versus English poetry with reference to Al-Sayyab and T. S. Eliot as two poles of modern poetry in Arabic and English. This study tried to shed light on the frequency of the conceptual metaphors in Al-Sayyab’s The Rain Song versus Eliot’s The Waste Land. Besides, it aimed to explore the similarities and differences between the two poems in using the CMT orientational ’Up’ and ’Down’ strategy. However, to accomplish its aims, this study adopted Lakoff and Jonson’s Conceptual Metaphor Theory ’CMT’ (1980); this theory asserted that metaphor is an inborn mental system in which we understand a certain concept in terms of another by drawing a logical mapping between the source domain and the target one. Finally, the study found that modern poetry was wealthy of conceptual metaphors. It also discovered that The Rain Song involved 65.29% conceptual metaphors of its total lines, so it exceeded The Waste Land which comprised only 39.40%. Furthermore, the study revealed that the two poems were generally pessimistic in which the ’Down’ domain exceeded the ’Up’ one in each poem. Also, it detected that Eliot was more pessimistic than Al Sayyab who was more optimistic. Keywords: conceptual metaphor, orientational metaphor, pessimistic, ’Up and Down’ strategy